Pyrimidine nucleoside analogues.X. 5-Substituted 1-(1,3-dihydroxypropyl-2) uracils. - Hiller, S A (1976)
A convenient method is suggested for synthesis of uracil-1-malonic acid diethyl ester by alkylating 2,4-bis(trimethylsilyl) uracil with bromo-malonic acid diethyl ester. This compound has been shown to hydrolyze with NaOH yielding either uracil or uracil-1-acetic acid, depending on reaction conditions. Similarly, thymine-1-malinic acid diethyl ester and 5-fluorouracil-1,3-dimalonic acid tetraethyl ester were obtained. 1-(1,3-Dihydroxypropyl)uracil has been obtained by reducing uracil-1-malonic acid diethyl ester with NaBH4.